THE EFFECT OF USE FLASH CARD WITH COOPERATIVE LEARNING MODELS TYPE NHT TOWARDS LEARNING ACTIVITY AND MATTER SUBJECT MASTERY OF VIRUS - IKomang Sutawijaya; arwin achmad; rini marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
Observation results show that mastery of the Virus subject matter on grade X Swadhipa’s student Senior High School in Natar is still low. This research aims to know the influence of the using picture cards media on students learning activities and mastering of the Virus subject matter for students. This research was quasi experimental design with unequivalent pretes postes group. The research samples are grade X1 and X2 which are selected from population by cluster random sampling. This research data is in quantitative and qualitative data. Quantitative data is obtained from the average of pretes and postes value which is analyzed statistically with t-test at 95% confidence levels using SPSS 17 program. Qualitative data is analyzed by descriptive analysis in percentage value. The research data is obtained from the student activity observation forms, and students' responses on using of flash cards media with NHT model. The research result shows that the average of mastering on subject by group students experiment is greater than control group (experiment = 79,1; control = 70,20). Moreover, the average of increasing the mastery of all observation indicators are greater than class control (experiment = 48,28; control = 43,22). The average of increasing percentage of student activity to all obeservation aspects in class experiment are greater than class control (experiment = 85,18; control = 76,30). In addition, the majority of students give positive response on using of flash cards media. Thus, learning process use flash card media with NHT learning model effects to improve the learning activity and mastery of the Virus subject matter on students.  Keywords: Flash Card, NHT, Learning Activity, Mastering Subject, Virus